PERSEPSI GURU AGAMA HINDU TERHADAP KENAKALAN SISWA SAAT PEMBELAJARAN DARING: Studi Kasus di SMAS Dharma Praja Denpasar - Kompyang Sri Wahyuningsih (Pangkaja: Jurnal Agama Hindu, 2021)
Online learning is currently still being implemented at every level of education in Indonesia in order to prevent the spread of the Covid-19 virus which is increasingly spreading in several areas, including Bali and Denpasar as the center of the economy. One of the senior high schools that implement online learning is SMAS Dharma Praja Denpasar. This raises various problems among students, namely behavior patterns that do not reflect politeness and noble character such as not being interested in online learning, not taking online learning seriously, even doing things that tend to be negative or naughty with various causative factors. This phenomenon is interesting to study in the realm of Hindu religious education.The purpose of this study was to reveal the perception of Hindu religious teachers on student misbehavior during online learning. The design in this research is a phenomenological case study with a qualitative approach. Data collection methods in this study were observation, interviews and literature study. The results of the study on the perceptions of Hindu religious teachers at SMAS Dharma Praja Denpasar related to student delinquency during online learning, namely: 1) Student delinquency is a violation of school rules and deviant behavior so that it can harm other students and make the learning atmosphere not conducive; 2) The category of student delinquency is divided into 2 parts, namely serious delinquency and disruptive behavior. Serious delinquency is perceived to include: stealing and truancy; while disruptive behavior includes: not paying attention to the teacher's explanation, cheating and disobeying the teacher's directions; 3) There are four causes of student delinquency, namely: lack of parental attention (moral education and economic support), teacher learning methods that are less varied (monotonous), language that is difficult for students to understand and too much subject matter; 4) How to overcome student delinquency, namely: verbal reprimand, special attention, manipulating assignments, providing substitute activities, providing special understanding, providing learning grids, communicating with parents, giving rules, giving good and bad choices, refraction, providing experience fail, provide motivation, communicate privately with students and are returned to parents.